Analisis faktor-faktor yang mempengaruhi minat mahasiswa terhadap layanan digital banking: Studi kasus pada Bank Syariah Indonesia - Noviana, Velani Laily (Maliki Interdisciplinary Journal, 2026)
This study investigates the factors influencing students’ interest in adopting digital banking services at Bank Syariah Indonesia (BSI). The ongoing digital transformation in the financial sector positions students, particularly Generation Z, as a crucial and strategic market segment. A quantitative research method was employed by distributing questionnaires to students at UIN Maulana Malik Ibrahim Malang. Data analysis was conducted by examining the correlations between Islamic financial literacy, perceived ease of use, and perceived usefulness in relation to students’ interest in utilizing digital banking services. The findings reveal that both Islamic financial literacy and the ease of digital access significantly affect students’ adoption of digital banking. These results highlight the importance of strengthening financial literacy and enhancing mobile banking features to foster greater financial inclusion among academic communities. Consequently, the study recommends the integration of more educative elements within mobile banking applications to support financial awareness and broaden the reach of Islamic banking services in higher education institutions.